Assessment of depression, anxiety, stress, and cognitive parameters in medical students: A pilot study - Shomi Anand; Kirti Hemwani; Sonu Ajmani; Sai Sailesh Kumar Goothy; Anita Choudhary (Asian Journal of Medical Sciences, 2023)
Background: As there is an increase in mental health issues among medical students, it is mandatory to assess their mental health status. In our earlier studies, we observed differences in the scores of depression, anxiety, and stress between male and female students. Aims and Objectives: The present study was undertaken to assess depression, anxiety, stress, and cognitive parameters in male and female medical students. Materials and Methods: A total of 100 medical students’ males (n=50) and females (n=50) were part of the study after obtaining voluntary, written informed consent. The required sample size for the study was 97 with a 95% of confidence level, 10% of margin of error, and 50% of the population proportion. This means 97 or more measurements/surveys are needed to have a confidence level of 95% that the real value is within ±10% of the measured/surveyed value. Depression, anxiety, and stress were assessed using the DASS 21 questionnaire. Spatial and verbal memory test was administered to assess the cognitive functions. Results: The depression scores were significantly higher (P<0.0001) in females when compared with males. Anxiety scores were significantly higher in females when compared with males (P<0.0001). Stress scores were significantly higher (P<0.0001) in females when compared with males. Spatial (P<0.0001) and verbal (P=0.0141) memory was significantly higher in females when compared with males. Conclusion: There were significantly higher levels of depression, anxiety, and stress scores in female students when compared with males. Further, spatial and verbal memory was also higher in females. There is a strong need for further detailed studies in this area and for adopting adequate management methods to manage negative psychological emotions in females.